Hereditary Hemorrhagic Telangiectasia: anesthetic considerations in urgent amputation: Implicações Anestésicas da Telangiectasia Hemorrágica Hereditária - Domingues, Cátia (Journal of the Portuguese Society of Anesthesiology, 2024)
Hereditary Hemorrhagic Telangiectasia (HHT), or Osler-Weber-Rendu syndrome, is an uncommon genetic disorder characterized by vascular dysplasia, resulting in vascular wall fragility and the formation of vascular lesions in various organs. The authors describe the case of an 87-year-old woman with HHT, iron-deficiency anemia, and heart failure, undergoing urgent surgery for the amputation of the right lower limb due to acute ischemia. Regional anesthesia, using ultrasound-guided block of the femoral and subgluteal sciatic nerves, proved effective and safe, avoiding potential complications associated with general anesthesia. The patient had a satisfactory recovery without the need for perioperative transfusion. The authors highlight the anesthetic challenges associated with HHT and emphasize the importance of careful planning to control bleeding, hemodynamic status, and oxygenation in patients with this condition, ensuring effective pain management.